A DATA-DRIVEN APPROACH TO DESIGNING NEW SERVICES FOR VEHICLE OPERATIONS MANAGEMENT - Kim, Min-Jun; Lim, Chiehyeon; Kim, Kwang-Jae (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Various types and massive amounts of data are collected in the automotive industry. Such data proliferation facilitates and improves the design of services for vehicle operations management (VOM). A VOM service is a service that helps drivers drive safely, conveniently, and pleasurably with the use of VOM-related data. Despite the applicability of big data to VOM service design, few efforts have been made to establish a big data-based design process for VOM services. To fill the research gap, this study proposes an approach to analyzing and utilizing VOM-related data for designing VOM services. The proposed approach aids service designers in designing VOM services by using VOM-related data. A case study on the design of an eco-driving service, a popular VOM service, is presented to demonstrate the feasibility and effectiveness of the approach. The proposed approach could facilitate the design of VOM services and provide a foundation for data-driven service innovations.